Enfrentamento da violência no território das juventudes: a potência dos círculos dialógicos para a tessitura de saberes nas aulas de educação física escolar - Cunha, Halisson Mota (2022)
This research presented powerful elements to face the manifestations of violence inside the youth bell tower, set in the school setting of the Liceu do Conjunto Ceará (LCC) in the city of Fortaleza. The general objective was to reflect the power of the collaborative work proposal with the perspective of the dialog with the youths in the face of the manifestations of violence in the school environment of the LCC. Thus, the specific objectives were: a) To understand the concepts that LCC youths bring with them about violence; b) Describe the dilemmas felt and experienced by young people in the face of the various manifestations of violence that hover in their daily lives; c) Point out the potential for the use of school physical education (EFE) as a strategy to face VE in the setting of the LCC; d) Socialize the potency of Dialogical Circles in stimulating the autonomy and protagonism of young people in the face of facing EV. The theoretical-methodological approach had a qualitative character, using the component of the collaborative dialectic of intervention, and which were arranged in an intervention proposal, containing 3 modules with six meetings. The research took as central collaborators the youths of the 2nd year of high school at the LCC school. One class from each shift was indicated to participate, making a total of 3 classes (morning, afternoon and evening). Among the procedures used during the meetings, we used: dialogic circles based on the proposal of Figueiredo (2003) and the experiential narratives of the young participants. We realized that different types of violence hover over the young people's lived world, branching out and being practiced in the school environment; We feel how the violence of “Bullying” leaves deep marks, being able to propagate itself in time and space; We observed the EFE, in view of its contents, as a powerful way to face the VE; And we indicate, in this study, the potency of dialogic circles as a fundamental component to stimulate the autonomy and the protagonism of young people to overcome the limit-situations in the face of their contexts. In general, it was also noticed that the LCC school has been a place of protection for the youth, as its pedagogical actions stimulate democratic, participatory and inclusive practices, enabling an integral formation of young employees. Another determining factor for the school to tread paths to confront violence was the development of interdisciplinary projects, which work on current themes and contextualized in the reality of the community. We conclude that: a) This research has the potential to be worked in a network, within the reality of basic education in Ceará, to face VE; b) Dialogical circles are fundamental within a collaborative perspective to stimulate partner knowledge and motivate young people's autonomy in facing different problems and possible situations of violence; c) We indicate the EFE component as one of the educational possibilities to face EM in the youth scenario. We point out in this thesis, in the time and space of its making, that the scenario of youths set in the LCC school has the power to deal with the confrontation of VE.